2006
DOI: 10.2353/jmoldx.2006.050053
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Human Platelet Antigens 1 to 6 and 15 by High-Resolution Amplicon Melting and Conventional Hybridization Probes

Abstract: High-resolution melting techniques are a simple and cost-effective alternative to other closed-tube genotyping methods. Here, we genotyped human platelet antigens (HPAs) 1 to 6 and 15 by high-resolution melting methods that did not require labeled probes. Conventional melting analysis with hybridization probes (HybProbes) was also performed at each locus. HybProbe assays were performed individually, whereas amplicon melting (HPAs 1 to 5 and 16) and unlabeled probe (HPA 6) assays were duplexed when possible. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 30 publications
(26 reference statements)
1
29
0
1
Order By: Relevance
“…[33] since this is a closed-tube assay (does not require additional precautions to prevent crossover of PCR products), avoids sequencing processes, laborious procedures and high costs as well as offering robust and high efficiency in its results [25,34]. On average, this type of test has been calculated to be three times faster and five times cheaper than other types of analysis such as MLST and RFLPs [17].…”
Section: Resultsmentioning
confidence: 99%
“…[33] since this is a closed-tube assay (does not require additional precautions to prevent crossover of PCR products), avoids sequencing processes, laborious procedures and high costs as well as offering robust and high efficiency in its results [25,34]. On average, this type of test has been calculated to be three times faster and five times cheaper than other types of analysis such as MLST and RFLPs [17].…”
Section: Resultsmentioning
confidence: 99%
“…42 With small PCR products, homozygous variants are distinguished by Tm and heterozygotes are identified by melting curve shape. The method has been applied to many common clinical single-base variants 43 and compared against dual-hybridization probes 44 and unlabeled probes. 45 However, many small insertions/deletions and some single base changes can be difficult to distinguish from wild type when homozygous.…”
mentioning
confidence: 99%
“…Amplicon melting monitored with a DNA dye uses temperature for multiplexing instead of probe color. Prior multiplex genotyping via amplicon melting has been limited to duplex assays (15,31 ). We have demonstrated that the method can be multiplexed to at least 4 amplicons.…”
Section: Discussionmentioning
confidence: 99%